To Live during War: On the Book of A. Forrest. Review of: Forrest, A. (2022). Za kromkoi polia boia. Zhizn’ voennykh vo vremena Revoliutsionnykh i Napoleonovskikh voin [Beyond the Battlefield. The Life of the Military during the Revolutionary and Napoleonic Wars]. Moscow: ROSSPEN. 280 p - Bolt, Valentina S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This essay considers Beyond the Battlefield, a book published by British historian Alan Forrest in 2022, which is a study of the military-anthropological history of the French Army during the First Republic and the First Empire. The book includes articles and reports by the prominent historian over the past eighteen years. Considering the similarities and differences between the Republican and then the Imperial army and the army of the Ancien Régime, A. Forrest studies the changed content of government propaganda aimed at attracting new recruits and maintaining high morale of soldiers; he demonstrates how the military reality differed from the recruits’ expectations; additionally, he investigates what exactly caused the fear, pleasure, or disappointment in the daily life of the military. The author of this essay analyses some of the theses put forward by A. Forrest, which are of particular interest to Russian specialists in military-historical anthropology and historical psychology in particular.